Areal-typological complexity of Lithuanian dialects - Kardelis, Vytautas (Lietuvių kalba, 2017)
This article deals with one of the most promising stages in Lithuanian dialectology discussed in the article “Seven stages of Lithuanian dialectology” published in the 2016 issue of the scientific electronic journal “Lietuvių kalba” (‘The Lithuanian Language’) (see Kardelis 2016). I referred to this stage as typological; however, now I think that the best term for this stage is the term areal-typological complexity (arealtypologische Komplexität) which originates from works by Alfred Lameli (2013). The concept of complexity is not associated with the attempt to classify dialects according to different “distinctive features” but rather with an idea, clearly supported by empirical facts that diatopical variation in language is highly complex. A closer look at the context of Lithuanian dialectology research reveals that the concept of complexity is still not discussed thoroughly; while specific studies are practically non-existent. The most general methodological principle which should be applied in carrying out an areal-typological study of the complexity of Lithuanian dialects could be referred to as the principle of offside. This means that studies of Lithuanian dialectology should offside from the conventionally applied research tradition and from: a) the aim to classify dialects typologically; b) all classifications of Lithuanian dialects published up to date; c) distinctive features described in the contemporary classification (as well as earlier classifications); d) the goal to specify the boundaries of dialects and subdialects. The second general theoretical criterion is related to the approach to the linguistic system. Here I rely on the concept of a diasystem introduced into the field of dialectology by Uriel Weinreich (1954; 1974). The whole area of the Lithuanian language together with its diatopical variants may be interpreted as a diasystem of Lithuanian which consists of separate systems. The most suitable, convenient and universal criteria for the analysis of empirical data established by the long-standing theory and practice of research into phonology are the following: 1) the quality of the elements of a vocalism system; 2) the quantity of the elements of a vocalism system; 3) the interrelationship between the quality and quantity of a vocalism system. Since here we are dealing with the Lithuanian language which features a complex prosodic system, we must introduce an additional criterion, i.e. 4) stress. Empirical data for the present study were collected from modern, phonological “grammars of dialects”. This article does not encompass the whole diasystem of the Lithuanian language since it only tackles the area covered by the Aukštaičiai dialect. The main phonological qualities according to which the basic vocalism model of the diasystem of the Aukštaičiai dialect can be described are the following: 1) the system of long vowels in the stressed position; 2) the shift in the level of rise of low vowels; 3) the system of short vowels in the stressed position; 4) automatic qualitative shifts; 5) vowel reduction (three degrees). The basic vocalism model described in accordance with the above criteria rather clearly indicates that the great differentiation of Lithuanian dialects postulated in the works on Lithuanian dialectology only has a phonetic and not a phonological basis and it can only be based on the differences of phonetic features. A phonological approach to the diasystem of the Aukštaičiai dialect of Lithuanian does not reveal any radical or extreme differentiation. In addition, the model also shows another significant regularity. The more features are taken into account, the lower the occurrence of individual, less significant dialectal elements distinguished on the basis of one feature (in comparison to the classification by A. Girdenis and Z. Zinkevičius). This approach thus allows solving the complexity of the puzzle of Lithuanian dialects (or, rather the complexity of the diasystem of the Aukštaičiai dialect of Lithuanian) which is summarised in Figure 10. As the matrix in Figure 9 illustrates, the diasystem of the Aukštaičiai dialect of Lithuanian so far consists of three zones represented in the matrix by three different colours.
Keywords: dialectology; areal-typological complexity; diatopical variation; basic vocalism; classifications of Lithuanian dialects; diasystem